Change in Population Characteristics and Teen Birth Rates in 77 Community Areas: Chicago, Illinois, 1999–2009. (July 2015) - Gunaratne, Shauna; Masinter, Lisa; Kolak, Marynia; Feinglass, Joe
Objective: We analyzed community area differences in teen births in Chicago, Illinois, from 1999 to 2009. We analyzed the association between changes in teen birth rates and concurrent measures of community area socioeconomic and demographic change. Methods: Mean annual changes in teen birth rates in 77 Chicago community areas were correlated with concurrent census-based population changes during the decade. Census measures included changes in race/ethnicity, adult high school dropouts, poverty or higher-income households, crowded housing, unemployment, English proficiency, foreign-born residents, or residents who moved in the last five years. We included non-collinear census measures with a p <0.1 bivariate association with change in teen births in a stepwise multiple linear regression model. Results: Teen birth rates in Chicago fell faster than the overall birth rates, from 85 births per 1, 000 teens in 1999 to 57 births per 1, 000 teens in 2009. There were strong positive associations between increases in the percentage of residents who were black and Hispanic, poor, without a high school diploma, and living in crowded housing, and a negative association with an increase in higher-income households. Population changes in poverty, Hispanic population, and high school dropouts were the only significant measures in the final model, explaining almost half of the variance in teen birth rate changes. Conclusion: The study provides a model of census-based measures that can be used to evaluate predicted vs. observed rates of change in teen births across communities, offering the potential to more appropriately prioritize public health resources for preventing unintended teen pregnancy.